Associations among physical activity tracking, physical activity motivation and level of physical activity in young adults. (July 2022) - O'Loughlin, Erin K; Sabiston, Catherine M; deJonge, Melissa L; Lucibello, Kristen M; O'Loughlin, Jennifer L
Whether physical activity (PA) tracking devices are associated with PA motivation in young adults is largely unknown. We compared total PA minutes per week, total minutes walking/week, meeting moderate-to vigorous PA guidelines, and past-year activity tracking across motivation cluster profiles among 799 young adults. Participants with "self-determined" profiles reported the highest total PA minutes/week followed by participants with "low intrinsic, " "controlled self-determined, " and "high external" proﬁles. A behavior regulation profile X activity tracking frequency interaction was not significant. Behavior regulation profiles may need to be considered in PA interventions using activity trackers.